NEW INEQUALITIES FOR APPROXIMATELY h CONVEX FUNCTIONS PERTAINING GENERALIZED FRACTIONAL INTEGRALS - Kashuri, Artion; Budak, Hüseyin; Kapucu, Rabia; Liko, Rozana (Matematichki Bilten, 2022)
In this paper, we first establish some new Hermite-Hadamard type inequalities for approximately \(h\)-convex function by using generalized fractional integrals. Also, some midpoint and trapezoid type inequalities for approximately \(h\)-convex functions via generalized fractional integrals are presented. At the end, a briefly conclusion is given. Our results may stimulate further research in different areas of pure and applied sciences.